Predictive relationships of information technology utilization, work discipline, and workload with employee performance at the environmental agency of Tanjungbalai City - Rafika Ayu Nasution; Surya Bakti (Privietlab, 2026)
The digital transformation of public administration has reshaped the daily conditions under which civil servants or Aparatur Sipil Negara (ASN) deliver public services. However, the association between technological, behavioral, and demand-side factors and employee performance in local government agencies remains insufficiently explored. This study examined the simultaneous and partial predictive relationships between information technology utilization, work discipline, and workload with self-reported employee performance at the Environmental Agency or Dinas Lingkungan Hidup of Tanjungbalai City, Indonesia. A quantitative, associative, cross-sectional, and non-experimental survey design was employed. Primary data were collected using a five-point Likert questionnaire administered to civil servants at the agency. Of the 35 ASN, 34 returned complete and usable responses, producing a near-census with one non-response. Data were analyzed using multiple linear regression after validity, reliability, and classical assumption testing in IBM SPSS Statistics. The findings indicate that the three predictors jointly explain 46.3% of the variance in self-reported employee performance (F (3, 30) = 8.635, p <.001). The partial pattern was positive and statistically significant: work discipline was the strongest predictor (β = .383, p = .013), followed by information technology utilization (β = .346, p = .028) and workload (β = .296, p = .049). Because this study was cross-sectional and based on self-reports, these results should be interpreted as perceived or predictive associations rather than definitive causal effects. The positive workload coefficient is interpreted cautiously within the observed workload range and does not imply that increasing the workload generally improves performance; an excessive workload may still impair performance. The theoretical and managerial implications for human resource management in local government agencies are discussed.